2011
DOI: 10.1103/physrevb.83.144527
|View full text |Cite
|
Sign up to set email alerts
|

Diamagnetism, Nernst signal, and finite-size effects in superconductors above the transition temperatureTc

Abstract: Various superconductors, including cuprate superconductors, exhibit peculiar features above the transition temperature Tc. In particular the observation of a large diamagnetism and Nernst signal N in a wide temperature window above Tc attracted considerable attention. Noting that this temperature window exceeds the fluctuation dominated regime drastically and that in these materials the spatial extent of homogeneity is limited, we explore the relevance of the zero dimensional (0D)-model, neglecting thermal flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The H dependence of M d , the diamagnetic component of magnetization, is very similar to that of N sc (ref. 21), as expected theoretically 16,22 . Magnetization data on an underdoped sample of Bi-2201 with T c = 12 K (ref.…”
Section: Nernst Effect and Diamagnetism In Bi-2201supporting
confidence: 50%
“…The H dependence of M d , the diamagnetic component of magnetization, is very similar to that of N sc (ref. 21), as expected theoretically 16,22 . Magnetization data on an underdoped sample of Bi-2201 with T c = 12 K (ref.…”
Section: Nernst Effect and Diamagnetism In Bi-2201supporting
confidence: 50%
“…Scanning tunneling spectroscopy studies 135,136 of Bi 2 Sr 2 CaCu 2 O 8+δ have indicated a granular character to superconducting correlations above T c , and a scanning magnetometry study 137 of an LSCO film found inhomogeneous magnetic domains that survived to T c + 60 K. The electronic inhomogeneity may be a necessary ingredient to explain the large magnitude of ρ ab in the normal state. Indeed, Schneider and Weyeneth 138 have recently presented an analysis of the diamagnetism and Nernst signal based on a granular picture. Similarly, there has been an estimate of the diamagnetism from fluctuating stripes.…”
Section: 128mentioning
confidence: 99%
“…However, it should be kept in mind that the observed strong diamagnetism and Nernst signal in a wide temperature window above T c exceeds the fluctuation dominated regime drastically. Indeed, taking the inhomogeneities of single crystals into account, the effective dimensionality is reduced to zero and reduced dimensionality enhances the thermal fluctuations [42]. Nonetheless, the proven existence of copper pairs above T c implies that they contribute to the transport properties and with that modify the standard Fermi liquid picture.…”
Section: Discussionmentioning
confidence: 99%